Sort by

- Relevance
- |Time

**u**= 8i + 7j → tan(**u**) = 7/8 v = 7i - j → tan(v) = - 1/7 tan(a - b) = sin(a - b) / cos(a - b...tan(b)] / [1 + tan(a).tan(b)] → adapt this result to your case tan(**u**- v) = [tan(**u**) - tan(v)] / [1 + tan(**u**).tan(v)] tan(**u**- v) = [(7/8) - (- 1/7...2 Answers · Science & Mathematics · 29/04/2019

a)

**u**-3v multiplying vextors by a scalar number such as 3 simply... vectors is <x1±x2,y1±y2>.**u**-3v=<3-(-6),1-18> = <9,-17> b) We use...1 Answers · Science & Mathematics · 29/04/2019

If v is half of w: v = w/2 and

**u**is the mean of v and w:**u**= (v + w) / 2 And you...240 w = 80 Now that we have w we can solve for v and**u**: v + w = 120 v + 80 = 120 v = 40**u**= (v + w) / 2**u**= (40 + 80...3 Answers · Science & Mathematics · 25/10/2019

You were doing fine. I would not try to factor anything. Just proceed with the substitutions.

**u**= 2x³ + 6x du/dx = 6x² + 6 du = (6x² + 6) dx ∫ (6x² + 6)sin(2x³ + 6x) dx = ∫ sin(**u**) du1 Answers · Science & Mathematics · 31/08/2019

8u - 8 = 4 - 4w 8u + 4w = 12 2u + w = 3 w = 3 - 2u w =

**u**+ v 3 - 2u =**u**+ v v = 3 - 3u 8u = 4 + 6v 8u = 4 + 6 * (3 - 3u) 4u = 2 + 3 * (3 - 3u) 4u = 2 + 9 - 9u 13u = 11**u**= 11/13 v = 3 - 3u v = 3 - 33/13 v = 39/13 - 33/13 v = 6/13 w =**u**+ v w = 11/13 + 6/13 w = 17/132 Answers · Science & Mathematics · 16/09/2019

...(a < X<b) = ∫ f(x(y)) dx/dy dy range

**U**(0) to**U**(1) = changes to η at one end = = -ln(1−0)/λ = 0 η at...1 Answers · Science & Mathematics · 10/01/2020

**u**= - 9 i + 13 j I**u**I = [ 81 + 169 ]^(1/2) I**u**| = 250^(1/2) = 5 √104 Answers · Science & Mathematics · 29/04/2019

...39;∩B' , so n(A∪B) + n(A'∩B') = n(

**U**) n(A∪B) + 21 = 90 n(A∪B) = 90 - 21 n(A∪...2 Answers · Science & Mathematics · 17/09/2019

It's an isosceles triangle so

**u**and v are equal and Pythagoras requires that u²...9 Answers · Science & Mathematics · 19/07/2019

### Suppose that

**u**=log[base10](4) and v=log[base10](5). Find log[base10](√1000) in terms of**u**and/or v.?...2^2) + (3/2) * log[10](5) => (3/4) * log[10](4) + (3/2) * log[10](5) => (3/4) *

**u**+ (3/2) * v2 Answers · Science & Mathematics · 25/07/2019